(untitled) - Max, Douglas (New York, 2003)
Writing performance appraisals is one of the most difficult and time-consuming tasks managers face. Perfect Phrases for Performance Reviews simplifies the job, providing a comprehensive collection of phrases that managers can use to describe employee performance, provide directions for improvement, and more. For example: "Sets priorities well" . "Misses important deadlines"
Keywords: Người lao động,Employees,Employees; Thuật ngữ,Rating of,Terminology